2021
DOI: 10.3389/fonc.2021.666815
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Damage Response Pathway in Ovarian Clear Cell Carcinoma

Abstract: Ovarian clear cell carcinoma (OCCC) is one of the major types of ovarian cancer and is of higher relative prevalence in Asians. It also shows higher possibility of resistance to cisplatin-based chemotherapy leading to poor prognosis. This may be attributed to the relative lack of mutations and aberrations in homologous recombination-associated genes, which are crucial in DNA damage response (DDR), such as BRCA1, BRCA2, p53, RAD51, and genes in the Fanconi anemia pathway. On the other hand, OCCC is characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 161 publications
(171 reference statements)
1
15
0
Order By: Relevance
“…6 Clear cell carcinoma has many genetic mutations in the AT-rich interaction domain 1a (ARID1A) gene, phosphatidylinositol-4,5-biphosphate 3-kinase catalytic alpha subunit, phosphatase and tensin homolog, and microsatellite instability. 23 The CA-125 level can reflect the patient's tumor burden and an elevated level indicates disease progression. 24 The results of this study confirm with a study in 303 patients which showed CA-125 was significantly associated with recurrence and affects DFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…6 Clear cell carcinoma has many genetic mutations in the AT-rich interaction domain 1a (ARID1A) gene, phosphatidylinositol-4,5-biphosphate 3-kinase catalytic alpha subunit, phosphatase and tensin homolog, and microsatellite instability. 23 The CA-125 level can reflect the patient's tumor burden and an elevated level indicates disease progression. 24 The results of this study confirm with a study in 303 patients which showed CA-125 was significantly associated with recurrence and affects DFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…About 10% of ovarian cancer patients were found to be associated with genetic risk and the first known susceptibility genes are BRCA1 and BRCA2 [ 6 , 7 ]. Other HRR pathway-related genes (ATM, ATR, CDK12, FANCA, FANCD2 and RAD50) were also found to play an essential role in ovarian cancer pathogenesis [ 8 , 9 ]. Due to the limited knowledge about the molecular etiology of ovarian cancer, if only the BRCA1/2 gene is tested, more than 5% of patients with deleterious variants in other known risk genes will be missed [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian clear cell carcinoma (OCCC) is rare, with higher prevalence in Asian populations, and characterized by chemoresistance and poor prognosis. 85 However, pre-clinical evidence suggests PARPi may act as potent chemosensitizers in OCCC 86 and is reviewed in more detail in. 85 Due to its low prevalence, it is challenging to extrapolate data from the small numbers of OCCC patients included in clinical trials of antiangiogenic and immunotherapy agents, although the current evidence is reviewed by Ogasawara et al 87 The same issue plagues the mucinous subtype, with a paucity of cases present in large clinical trials limiting the reliability of conclusions from subtype-specific analysis.…”
Section: Other Histological Subtypesmentioning
confidence: 99%
“… 85 However, pre-clinical evidence suggests PARPi may act as potent chemosensitizers in OCCC 86 and is reviewed in more detail in. 85 Due to its low prevalence, it is challenging to extrapolate data from the small numbers of OCCC patients included in clinical trials of antiangiogenic and immunotherapy agents, although the current evidence is reviewed by Ogasawara et al 87 The same issue plagues the mucinous subtype, with a paucity of cases present in large clinical trials limiting the reliability of conclusions from subtype-specific analysis. Despite not reaching statistical significance; however, evidence from GOG-0241 and ICON-6 suggest potentially beneficial effects of bevacizumab and cediranib respectively and is reviewed in more detail in.…”
Section: Other Histological Subtypesmentioning
confidence: 99%